Secondary stroke prevention beyond antiplatelets: The role of colchicine and GLP-1RA – an ounce of prevention is worth a pound of cure - Milija D. Mijajlović; Natan M. Bornstein; Vuk Aleksić (Therapeutic Advances in Neurological Disorders)
Stroke remains a major global health concern, ranking as the second most common cause of death and the third leading cause of disability worldwide. Despite advances in therapy and management, ischemic stroke patients continue to face high risks of recurrence, cardiovascular events, and mortality. Effective secondary stroke prevention is critical, encompassing antithrombotic therapy, management of vascular risk factors such as hypertension, dyslipidemia, and diabetes mellitus, and conducting healthy lifestyle. Approximately 80% of strokes are ischemic, with a significant proportion attributable to large-artery atherosclerosis of the extra- and intracranial arteries, particularly in the internal carotid artery. Atherothrombotic strokes, linked to plaque rupture and thrombus formation, present a notably high risk of recurrence. Inflammatory and immune mechanisms play pivotal roles in both the initiation and progression of atherosclerosis and stroke. Colchicine, an anti-inflammatory agent, has shown potential in managing cardiovascular disease, though its effects on stroke reduction and prevention have been inconsistent across studies. Its possible protective role against stroke is attributed to its anti-inflammatory actions, which include disrupting microtubule dynamics, inhibiting immune cell movement, and lowering inflammatory markers like L-Selectin and E-Selectin, while also suppressing interleukin release. Glucagon-like peptide-1 receptor agonists (GLP-1RA) agents have emerged as effective therapies for type 2 diabetes with notable cardiovascular benefits. These agents enhance glucose control while also providing protective effects against atherosclerosis and stroke. GLP-1RA drugs work by mimicking the effects of GLP-1, a peptide that regulates insulin release and glucose metabolism. They also exhibit anti-inflammatory properties, potentially reducing stroke risk through mechanisms such as improved endothelial function and reduced plaque formation. Clinical trials have indicated that GLP-1RA agents can significantly lower the incidence of nonfatal strokes and major adverse events. This narrative review underscores the importance of targeting inflammation to reduce the risk of recurrent stroke, emphasizing recent studies on colchicine and GLP-1RA. It consolidates evidence regarding the efficacy of these agents in secondary stroke prevention; however, future studies are needed to further explore their mechanisms and roles in comprehensive stroke management strategies.